Fabrication and Characterization of Polylactic Acid (PLA) Microporous Film Coated with Gelatin and Chromolaena Odorate Leaf Extract for Wound Dressing Application - Phosri, Santi; Ruenrom, Marisa; Chanpluk, Sirima; Kanyabut, Chatchana; Charoeythornkhajhornchai, Pollawat; Yisarakun, Waranurin (Applied Science and Engineering Progress, 2025)
The infection of the skin wound is the cause of pain and difficult recovery. This work has developed wound dressing from microporous PLA film-coated gelatin from marrow bone and jellyfish with blended Chromolaena odorata leaf extract at low concentration to stimulate skin cell growth. The microporous PLA film was produced by solution method with different ratios between dichloromethane (CH2Cl2) and tetrahydrofuran (THF) at 25:35, 25:50, and 25:65, respectively. The optical microscope and scanning electron microscope (SEM) were used to analyze the pore size of microporous PLA film and its physical characteristics after coating with different gelatins by dip coating process. The wound dressing film was determined for cell viability after testing with NIH/3T3 and HaCaT in the culture cell plate. The testing method was followed by a 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay to measure cell stimulation and cell viability using a UV absorption technique after staining. The result shows that our wound dressing can stimulate both NIH/3T3 and HaCaT keratinocytes but with different characteristics due to the different releasing characters of gelatins and different responses of cell types depending on C. odorata leaf extract concentration. The microporous PLA film-coated gelatin from jellyfish revealed better skin cell growth in both NIH/3T3 and HaCaT keratinocytes than that of coated gelatin from marrow bone because of the continuous releasing rate after contact with water of gelatin from jellyfish. Moreover, C. odorata leaf extract which was used for reducing the inflammation of the cellular injury displayed toxic HaCaT keratinocyte at high concentrations but it did not affect the NIH/3T3 toxicity. Interestingly, it can stimulate the cell viability of NIH/3T3 until 3 mg/mL of C. odorata leaf extract concentration and displays constant cell viability afterward.